2021
DOI: 10.1093/jpids/piaa176
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pediatric Recurrent Bacterial Meningitis in Beijing Children’s Hospital, 2006–2019

Abstract: Background Few data on recurrent bacterial meningitis (RBM) in children are available. Here, we estimated the frequency of RBM in children and investigated the predisposing conditions, etiology, and clinical characteristics of RBM in children. Methods Cases of RBM in the Beijing Children’s Hospital medical record database between January 2006 and December 2019 were collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
0
12
2
Order By: Relevance
“…Among the most important causes of meningitis recurrence in this study: peritoneal cerebral shunt in 42.9% of them, skull fracture in 40% of them, and meningocele in 25% of them. Compared to a study conducted in China, the recurrence rate for those with a skull fracture was 20%, and for those with meningocele, it was 11% (12). The high rates in this study may explain the di culty in managing some of the previous predisposing lesions.…”
Section: Discussioncontrasting
confidence: 64%
“…Among the most important causes of meningitis recurrence in this study: peritoneal cerebral shunt in 42.9% of them, skull fracture in 40% of them, and meningocele in 25% of them. Compared to a study conducted in China, the recurrence rate for those with a skull fracture was 20%, and for those with meningocele, it was 11% (12). The high rates in this study may explain the di culty in managing some of the previous predisposing lesions.…”
Section: Discussioncontrasting
confidence: 64%
“…In 2019, a multicenter study of children with recurrent pneumococcal meningitis showed an incidence of 1.5% [ 4 ]. A recent study showed that RBM incidence in children in Beijing, China, was 2.3%, which is relatively uncommon [ 5 ]. This study analyzed the clinical manifestations, auxiliary examination, and therapeutic outcomes of 10 Chinese children with RBM admitted to Hebei Children's Hospital from 2012 to 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no consensus on when immunological investigations should be initiated in children with IPD. The decision on whether to do an immune evaluation in children with IPD is often based on a child’s age at presentation, the site of infection (with meningitis considered the highest risk 29 ), recurrent IPD 21,30,31 and the presence of ≥2 warning signs of IEI. 22,32 Some studies suggest that certain age groups have a greater likelihood of having an underlying IEI.…”
Section: Discussionmentioning
confidence: 99%